1979
DOI: 10.1159/000145013
|View full text |Cite
|
Sign up to set email alerts
|

Helical structure of the human umbilical cord

Abstract: The helical structure of the human umbilical cord has been studied on 528 full-term cords from normal deliveries, 18 cords from aborted and developmentally normal fetuses with a CR length of 1.2–19.5 cm, and 10 cords from monozygotic twins. In order to resolve the discrepancy in the nomenclature of the twist direction, a method has been suggested which takes into account the direction to which the fetus must have rotated to produce the twist. The incidence of the right helical pattern was 64.58%, of the left h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 3 publications
0
32
1
3
Order By: Relevance
“…According to Chaurasia (1979) the true aetiology of umbilical cord coiling is unclear, but it is thought to result from foetal movements as well as unequal vascular growth. 11 According to Percy Malpas (1966), helical structure of the cord results from the reciprocal action between the intrinsic structures of the vessel walls on the one hand and the pressure, volume and flow rate of foetal blood on the other. 12 Number of complete twists present in these undistorted cords ranged between 8 and 16.…”
Section: Number Of Coils Of the Umbilical Cordmentioning
confidence: 99%
“…According to Chaurasia (1979) the true aetiology of umbilical cord coiling is unclear, but it is thought to result from foetal movements as well as unequal vascular growth. 11 According to Percy Malpas (1966), helical structure of the cord results from the reciprocal action between the intrinsic structures of the vessel walls on the one hand and the pressure, volume and flow rate of foetal blood on the other. 12 Number of complete twists present in these undistorted cords ranged between 8 and 16.…”
Section: Number Of Coils Of the Umbilical Cordmentioning
confidence: 99%
“…Normal human umbilical cords have two small arteries and one large vein. Typically, the two arteries are spiraled around the vein, running a helical course through the umbilical cord [13][14][15], as shown in fig. 4.…”
Section: Natural Helical Structuresmentioning
confidence: 99%
“…It has been reported that the helical nature of the cord is possibly controlled by factors which may be partly genetic and partly environmental [15]. However, this configuration can vary, implying alterations to the blood supply.…”
Section: Natural Helical Structuresmentioning
confidence: 99%
“…The true etiology of umbilical coiling is unclear, but it is thought to result from fetal movement as well as unequal vascular growth. 37,38 It appears that umbilical coiling pattern is established in the first trimester, although the presence of a mixed coiling pattern and even reversal of coiling direction in third trimester has been demonstrated. 39 The normal umbilical cord coiling is approximately one coil per 5 cm of umbilical cord length, or 0.20-0.24 coils per cm.…”
Section: Umbilical Cord Coilingmentioning
confidence: 99%